The poverty of the Linnaean hierarchy : a philosophical study of biological taxonomy - Ereshefsky, Marc (Cambridge studies in philosophy and biology., 2001)
"The question of whether biologists should continue to use the Linnaean hierarchy is a hotly debated issue. Invented before the introduction of evolutionary theory, Linnaeus's system of classifying organisms is based on outdated theoretical assumptions and is thought to be unable to provide accurate biological classifications." "Marc Ereshefsky argues that biologists should abandon the Linnaean system and adopt an alternative that is more in line with evolutionary theory. He traces the evolution of the Linnaean hierarchy from its introduction to the present. Ereshefsky illustrates how the continued use of this system hampers our ability to classify the organic world, and then he goes on to make specific recommendations for a post-Linnaean method of classification." "Accessible to a wide range of readers by providing introductory chapters to the philosophy of classification and biological taxonomy, the book will interest both scholars and students of biology and the philosophy of science."--Jacket